Disulfiram Suppressed Peritendinous Fibrosis Through Inhibiting Macrophage Accumulation and Its Pro-inflammatory Properties in Tendon Bone Healing - Zhou, Qi; Wang, Wei; Yang, Fujun; Wang, Hao; Zhao, Xiaodong; Zhou, Yiqin; Fu, Peiliang; Xu, Yaozeng (Frontiers in Bioengineering and Biotechnology, 2022)
The communication between macrophages and tendon cells has a critical role in regulating the tendon-healing process. Yet, the mechanisms regulating macrophages to control peritendinous fibrosis are unknown. Our data showed a strong pro-inflammatory phenotype of macrophages after a mouse tendon-bone injury. By using a small molecule compound library, we identified an aldehyde dehydrogenase inhibitor, disulfiram (DSF), significantly promotes the transition of macrophage from M1 to M2 phenotype, and decreases macrophage pro-inflammatory phenotype. Mechanistically, disulfiram targets gasdermin D (GSDMD) to inhibit macrophage cell pyroptosis, interlukin-1β and high mobility group box-1 protein release. These proinflammatory cytokines and damage associated molecular patterns are essential for tenocytes and fibroblasts proliferation, migration and fibrotic activity. Deficiency or inhibition of GSDMD significantly suppressed peritendinous fibrosis formation around the injured tendon, accompanied by increased regenerated bone and fibrocartilage compared with wild-type littermates. Collectively, these findings reveal a new pathway of GSDMD-dependent macrophage cell pyroptosis in remodeling fibrogenesis in tendon-bone injury. GSDMD may represent a potential therapeutic target in tendon-bone healing.